Identification and quantitation of bioactive components from honeycomb (Nidus Vespae). (1st June 2020) - Zhao, Haoan; Zhu, Min; Wang, Keru; Yang, Erlin; Su, Jinlong; Wang, Qian; Cheng, Ni; Xue, Xiaofeng; Wu, Liming; Cao, Wei
Graphical abstract: Highlights: This study solved the problem of high value utilization of honeycomb. 76 bioactive components from hydro-ethanolic extracts of honeycomb (EHB) were tentatively identified by UHPLC-HRMS. Dominant 14 polyphenols and 17 free fatty acids were quantified in EHB. Antimicrobial activities test verified that EHB can inhibit G+ and G − bacteria. Abstract: Honeycomb ( Nidus Vespae ) as an agri-food waste in bee product industry is in soaring demand for high-value utilization. This study is dedicated to investigate the physicochemical properties, chemical composition, and nutritional value of honeycomb by determination of physicochemical parameters, total phenolic and total flavonoid contents, antioxidant capacity in vitro, and bioactive components. By using ultra high-performance liquid chromatography–high resolution mass spectrometry (UHPLC–HRMS) method, a total of 76 bioactive components from hydro-ethanolic extracts of honeycomb (EHB) were tentatively identified, where the principal ones are polyphenols and fatty acids, which were further quantified by LC–MS and GC–MS, respectively. Moreover, antimicrobial activities test has been conducted, verifying that EHB can inhibit both Gram-negative (G − ) bacteria and Gram-positive (G+) bacteria, which is beneficial for the high-value utilization of honeycomb.